Cardiac CaM kinase II genes δ and γ contribute to adverse remodeling but redundantly inhibit calcineurin-induced myocardial hypertrophy - Kreußer, Michael; Lehmann, Lorenz; Keranov, Stanislav; Hoting, Marc-Oscar; Oehl, Ulrike; Kohlhaas, Michael; Reil, Jan-Christian; Neumann, Kay; Schneider, Michael D.; Hill, Joseph A.; Dobrev, Dobromir; Maack, Christoph; et al. (Circulation, 2014)
Background—Ca2+-dependent signaling through CaM Kinase II (CaMKII) and calcineurin was suggested to contribute to adverse cardiac remodeling. However, the relative importance of CaMKII versus calcineurin for adverse cardiac remodeling remained unclear.Methods and Results—We generated double-knockout mice (DKO) lacking the 2 cardiac CaMKII genes δ and γ specifically in cardiomyocytes. We show that both CaMKII isoforms contribute redundantly to phosphorylation not only of phospholamban, ryanodine receptor 2, and histone deacetylase 4, but also calcineurin. Under baseline conditions, DKO mice are viable and display neither abnormal Ca2+ handling nor functional and structural changes. On pathological pressure overload and β-adrenergic stimulation, DKO mice are protected against cardiac dysfunction and interstitial fibrosis. But surprisingly and paradoxically, DKO mice develop cardiac hypertrophy driven by excessive activation of endogenous calcineurin, which is associated with a lack of phosphorylation at the auto-inhibitory calcineurin A site Ser411. Likewise, calcineurin inhibition prevents cardiac hypertrophy in DKO. On exercise performance, DKO mice show an exaggeration of cardiac hypertrophy with increased expression of the calcineurin target gene RCAN1-4 but no signs of adverse cardiac remodeling.Conclusions—We established a mouse model in which CaMKII’s activity is specifically and completely abolished. By the use of this model we show that CaMKII induces maladaptive cardiac remodeling while it inhibits calcineurin-dependent hypertrophy. These data suggest inhibition of CaMKII but not calcineurin as a promising approach to attenuate the progression of heart failure.
Gesehen am 14.07.2020